Best Vitelliform Dystrophy - Tjok Agung Purnama Wisesaputra (PT Kalbe Farma Tbk., 2020)
Best Vitelliform Dystrophy atau Best disease autosomal dominant maculopathy disebabkan oleh mutasi gen BEST1 (atau VMD2), yang terletak pada kromosom 11 dan mengkodekan protein bestrophin, protein ini terlokalisir pada membran plasma basolateral RPE. Individu Best disease sering menunjukkan lesi makula berwarna kuning, seperti kuning telur. Penyakit ini cenderung muncul pada periode anak-anak atau dewasa muda, Sampai saat ini belum ada pengobatan untuk Best disease. Best Vitelliform Dystrophy or Best disease is an autosomal dominant maculopathy caused by mutations in the BEST1 (or VMD2), which is located on chromosome 11 and encodes the protein bestrophin, this protein localizes to the basolateral plasma membrane of the RPE. Affected individuals frequently show a yellow macular lesion, like egg yolks. This disease tends to present in children or young adults. Until now there has been no treatment for Best disease.